2007
DOI: 10.1364/oe.15.013936
|View full text |Cite
|
Sign up to set email alerts
|

Origin of coupling to antisymmetric modes in arc-induced long-period fiber gratings

Abstract: We study the origin of antisymmetric perturbation of the fiber in arc-induced long-period gratings that couple the core mode into the antisymmetric cladding modes. We demonstrate that this perturbation is caused by the temperature gradient in the fiber, which is induced, in turn, by the temperature gradient in the arc discharge. The reproducibility of the process of the grating inscription is higher when the fiber is placed in a region with larger temperature gradient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 10 publications
2
45
0
2
Order By: Relevance
“…The major discrepancy is the larger bandwidth of the real resonances that can be due to the fact that in the experiment we are dealing with leaky-modes. It should be mentioned that in our previous investigations concerning arc-induced gratings in the SMF28 fibre, from Corning, and in the PS1500 fibre, from FIBERCORE [10,11] the simulation spectra also fits fairly well the experimental ones. Moreover, for the latter fibre, where we were able to write a grating exhibiting a dual set of resonances formed by different mechanisms and caused by coupling to cladding modes of different symmetries, we have demonstrated that the resonances at shorter wavelengths belong to an asymmetric perturbation and the ones at longer wavelengths belong to a symmetric perturbation [17].…”
Section: Simulation Of the Grating Spectrumsupporting
confidence: 73%
See 2 more Smart Citations
“…The major discrepancy is the larger bandwidth of the real resonances that can be due to the fact that in the experiment we are dealing with leaky-modes. It should be mentioned that in our previous investigations concerning arc-induced gratings in the SMF28 fibre, from Corning, and in the PS1500 fibre, from FIBERCORE [10,11] the simulation spectra also fits fairly well the experimental ones. Moreover, for the latter fibre, where we were able to write a grating exhibiting a dual set of resonances formed by different mechanisms and caused by coupling to cladding modes of different symmetries, we have demonstrated that the resonances at shorter wavelengths belong to an asymmetric perturbation and the ones at longer wavelengths belong to a symmetric perturbation [17].…”
Section: Simulation Of the Grating Spectrumsupporting
confidence: 73%
“…At the same time, the gratings arc-induced in B/Ge fibres couple the core mode to the symmetric cladding modes as a result of induction of internal stresses (reversible structural rearrangement) [10,11]. The type of modes excited by arc-induced LPFGs in pure-silica-core fibres was not investigated previously.…”
Section: Simulation Of the Grating Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…The initial values of R co = 4.18 mm and Δn co-cl = 4.85 × 10 − 3 (at 1550 nm), which are close to the parameters of the standard fibre, have been obtained by taking into account the effect that the arc discharge has on the fibre properties [13] and they have been used to fit the spectrum in Ref. [3]. The computer simulation also indicates that diffusion contributes to an increase of the coupling strength.…”
Section: Resultsmentioning
confidence: 86%
“…On the other hand, considering the core-shift, i.e. the displacement of the core with respect to its normal central position in the fibre, as the origin of the grating formation [3], the same structural relaxation implies an increase of the coupling strength (the core-cladding refractive index difference increases). Note, however, that the LP 11 mode was initially over-coupled (the product of the coupling constant at the wavelength of the resonance centre and the grating length was larger than π/2) while the LP 12 and LP 13 modes became over-coupled during the first 20 h of annealing [4].…”
Section: Resultsmentioning
confidence: 99%